Isomorphic difference: Familiarity and distinctiveness in national research and innovation policies - Irwin, Alan; Vedel, Jane Bjørn; Vikkelsø, Signe (Research Policy, 2021)
Global research and innovation policies appear remarkably similar on a number of dimensions, including preferred principles of clustering and partnership, an emphasis on research-led growth and a focus on ‘hot topics’ such as nanotechnology and big data. However, policies for this field also reflect deeper-rooted traditions, institutional processes and ways of working: what looks the same can be very different when viewed in context. In this paper, we first consider the evidence for convergence across research and innovation policies before outlining perspectives based on contextual difference. Drawing particularly upon institutional theory, organizational studies and Science & Technology Studies (STS), we introduce the concept of ‘isomorphic difference’ as a means of symmetrically exploring relations of familiarity and distinctiveness. An illustration from Danish research and innovation policy is developed in order to bring together these conceptual but also policy-related issues. In addition, an initial analytical framework is presented. Finally, the relevance of ‘isomorphic difference’ to larger contemporary debates over the direction of research and innovation is summarized.